Troponin Variants as Markers of Skeletal Muscle Health and Diseases - Rasmussen, Monica; Jin, Jian-Ping (Frontiers in Physiology, 2021)
Ca2+-regulated contractility is a key determinant of the quality of muscle. The sarcomeric myofilament proteins are essential players in the contraction of striated muscles. The troponin complex in the actin thin filaments play a central role in the Ca2+-regulation of muscle contraction and relaxation. Among the three subunits of troponin, the Ca2+-binding subunit troponin C (TnC) is a member of the calmodulin super family whereas troponin I (TnI, the inhibitory subunit) and troponin T (TnT, the tropomyosin-binding and thin filament anchoring subunit) are striated muscle specific regulatory proteins. Muscle type-specific isoforms of troponin subunits are expressed in fast and slow twitch fibers and are regulated during development and aging, and in adaptation to exercise or disuse. TnT also evolved with various alternative splice forms as an added capacity of muscle functional diversity. Mutations of troponin subunits cause myopathies. Owing to their physiological and pathological importance, troponin variants can be used as specific markers to define muscle quality. In this focused review, we will explore the use of troponin variants as markers for the fiber contents, developmental and differentiation states, contractile functions, and physiological or pathophysiological adaptations of skeletal muscle. As protein structure defines function, profile of troponin variants illustrates how changes at the myofilament level confer functional qualities at the fiber level. Moreover, understanding of the role of troponin modifications and mutants in determining muscle contractility in age-related decline of muscle function and in myopathies informs an approach to improve human health.